Accessibility of largespace food stores - supermarkets and hypermarkets - in the Bratislava retail network in the concept of strategy Europe 2020 - Kita, Jaroslav
Aktuálna sieť maloobchodov v Bratislave. Dostupnosť supermarketov a hypermarketov v Bratislave. Geomarketing